Allelopathic effects of leaf powder from selected agroforestry tree species on the germination, growth, and yield of staple crops in a semiarid region - Berihu Abraha; Emiru Birhane; Tesfay Gidey; Abadi Tesfay; Zenebe Girmay Siyum; Gebreyohannes Grimay (Discover Applied Sciences)
Abstract Agroforestry (AF) systems improve ecological interactions and reduce environmental stresses in semiarid regions, thereby improving food security and livelihood. While many AF trees benefit crop growth, some may have inhibitory effects. Hence, assessing tree-crop interactions is essential to optimizing AF practices in semiarid regions. This study examines the allelopathic effects of Dodonaea angustifolia and Populus deltoides leaf powder on wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.) germination, growth, and yield. A pot experiment was conducted in Ganta Afeshum district, northern Ethiopia, using four concentrations of leaf powder (50, 100, 150, and 200 g per pot) mixed with soil, alongside a control (without leaf powder). Wheat germination and yield decreased by 10% and 15%, and 16 and 13%, respectively, as the concentrations of D. angustifolia and P. deltoides leaf powder increased to 200 g. Similarly, the addition of 200 g of D. angustifolia and P. deltoides leaf powder reduced barley germination by 13% and 14%, and its yield by 18% and 15%, respectively. These findings suggest that integrating D. angustifolia and P. deltoides into AF systems may reduce wheat and barley productivity in semiarid regions. Further long-term field studies are needed to confirm and expand upon these findings.